A basic theory of inheritance: How bad practice prevails - Vermeulen, Freek (Strategic Management Journal, 2018)
[Research Summary: This paper develops an inheritance theory explaining the diffusion and persistence of detrimental management practice. Received wisdom, in both management theory and practice, would suggest that a practice that lowers the life expectancy of adopting firms, over time, will vanish because it puts those firms at a competitive disadvantage. In this paper, I challenge this view. I develop a conceptual model that details how a practice that lowers the survival chances of adopting organizations may still spread and continue to exist across a population of firms. I propose that a combination of three basic conditions is sufficient to bring about this phenomenon: if the practice is somehow associated with success, if there exists causal ambiguity, and if the rate of its diffusion is high compared with the rate at which it accelerates firms' demise, the practice may continue to thrive and become a widespread and persistent feature in an industry. A pivotal conceptual insight is that the endurance of particular management practices and strategies is not merely a corollary of the competitiveness of the organizations that use them but that they have fitness levels of their own. Managerial Summary: All organizations have "best practices": habits that they have picked up in the past or mimicked from others. Managers often believe that these must be the best ways of doing things, because otherwise market forces would have eliminated them. The theory in the paper explains why this belief may be wrong. Some enduring practices may be harmful without managers realizing it because it is not necessarily the most optimal practices that survive (just like harmful viruses persist in nature). As a corollary, the paper discusses how the identification and cessation of detrimental practices can form a new source of and way to understand innovation.]